2014
DOI: 10.1186/1471-2415-14-4
|View full text |Cite
|
Sign up to set email alerts
|

Cataract subtype risk factors identified from the Korea National Health and Nutrition Examination survey 2008–2010

Abstract: BackgroundTo assess the socio-demographic and health-related risk factors associated with cataract subtypes in Korea.MethodsA total of 11,591 participants (aged ≥40 years) were selected from the Korean National Health and Nutrition Examination Survey between 2008 and 2010. The Korean Ophthalmologic Society conducted detailed ophthalmologic examinations on these participants based on the Lens Opacity Classification System III. Risk factors for developing any type of cataract, and its subtypes (nuclear, cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 48 publications
8
67
2
Order By: Relevance
“…Therefore, it is uncertain whether our results are relevant to other ethnic groups. Third, slit lamp examinations were performed by many different investigators, and an inter-observer variation could have been introduced, as already discussed in a previous study that used KNHANES data [44]. Despite this limitation, examinations were adequately performed by trained investigators, and risk factors associated with cataract were identified at a nation-wide level.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is uncertain whether our results are relevant to other ethnic groups. Third, slit lamp examinations were performed by many different investigators, and an inter-observer variation could have been introduced, as already discussed in a previous study that used KNHANES data [44]. Despite this limitation, examinations were adequately performed by trained investigators, and risk factors associated with cataract were identified at a nation-wide level.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in workers, but without a control group, was also considered (Cherian et al 2015). Four cross-sectional studies were conducted across relatively large samples of the general adult population to evaluate cataract risk factors (Burton et al 1997;Athanasiov et al 2008Athanasiov et al , 2010Rim et al 2014). In total, eight studies were conducted in groups of patients with cataract (Ughade et al 1998;Neale et al 2003;Mukesh et al 2006;Saadat & Farvardin-Jahromi 2006;Pastor-Valero et al 2007;Echebiri et al 2010;Theodoropoulou et al 2011;Zarei et al 2015).…”
Section: Study Selectionmentioning
confidence: 99%
“…[22][23][24][25][26] Briefly, ophthalmology residents performed comprehensive slitlamp eye examinations using a BQ 900 slitlamp (Haag-Streit AG). The standard Lens Opacities Classification Systems III (LOCS III) was used to assess cataracts.…”
Section: Age-related Cataract Assessmentsmentioning
confidence: 99%